Synthesis of the Reverse Transcriptase Inhibitor L-737,126 and the CB2 Cannabinoid Receptor Agonist Pravadoline by a Copper-Catalyzed Intramolecular Cross-Coupling - Gao, Detian; Back, Thomas G. (Synlett, 2013)
The conjugate additions of N-formyl-o-haloanilines to acetylenes activated by electron-withdrawing groups afford products which undergo subsequent intramolecular C-arylations mediated by copper(II) acetate in DMF to produce the corresponding indoles. These processes require no external ligands and can be carried out without protection from air or moisture. This procedure was applied to the concise syntheses of two pharmacologically interesting indoles: the anti-HIV agent L-737,126 and the antinociceptive CB2 cannabinoid agonist pravadoline.
Keywords: copper; cross-coupling; green chemistry; indoles; drugs